2019
DOI: 10.1371/journal.pone.0215350
|View full text |Cite|
|
Sign up to set email alerts
|

Estimating the value of tropical coastal wetland habitats to fisheries: Caveats and assumptions

Abstract: Habitat valuation can provide an objective basis for the prioritisation of conservation and restoration actions. The attribution of fisheries production to particular habitat units is an important measure of value, but is difficult to estimate. Using the case study of habitat use by juvenile banana prawns in a tropical estuary, we assessed the potential to produce valid value estimates at two spatio-conceptual scales: estuary reach and whole estuary. Additionally, we also explore the potential to produce meani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 88 publications
(139 reference statements)
0
17
0
Order By: Relevance
“…Ecological restoration or "the process of assisting the recovery of an ecosystem that has been degraded, damaged, or destroyed" (SER, 2004) is urgently needed to assist ecosystems where natural recovery is hindered or impeded (Perrow and Davy, 2002). Ecological restoration principally seeks to recover the functioning of degraded ecosystems, however restoration of marine and coastal habitats can provide a range of ecological and socio-economic benefits, such as coastal protection from flooding and erosion, fisheries habitat, water quality improvements, and carbon sequestration and storage (Duarte et al, 2013;Fodrie et al, 2017;Macreadie et al, 2017;Abrantes et al, 2019;Gilby et al, 2020). The United Nations General Assembly recently declared the "UN Decade on Ecological Restoration" for 2021-2030 and ecological restoration is on the rise as a component of the solution to ameliorate ecosystem degradation (Possingham et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Ecological restoration or "the process of assisting the recovery of an ecosystem that has been degraded, damaged, or destroyed" (SER, 2004) is urgently needed to assist ecosystems where natural recovery is hindered or impeded (Perrow and Davy, 2002). Ecological restoration principally seeks to recover the functioning of degraded ecosystems, however restoration of marine and coastal habitats can provide a range of ecological and socio-economic benefits, such as coastal protection from flooding and erosion, fisheries habitat, water quality improvements, and carbon sequestration and storage (Duarte et al, 2013;Fodrie et al, 2017;Macreadie et al, 2017;Abrantes et al, 2019;Gilby et al, 2020). The United Nations General Assembly recently declared the "UN Decade on Ecological Restoration" for 2021-2030 and ecological restoration is on the rise as a component of the solution to ameliorate ecosystem degradation (Possingham et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, estimates at the whole‐of‐estuary level, the seascapes level, in line with current understanding of estuarine species reliance on a mosaic of habitats (Nagelkerken et al ; Sheaves ), required a relatively low number of assumptions and produced estimates with relatively low variability. Abrantes et al () found as a conservative estimate, a maximum juvenile prawn biomass of 6.5 g/m 2 for the 2 m wide bands along the estuary edge where prawns are found. For the estuary studied, with an edge area of 5.6 ha, the conservative total biomass of juvenile pawns was 0.36 tonnes.…”
Section: Case Studiesmentioning
confidence: 97%
“…The east coast tropical study (Abrantes et al . ) found that estimates of productivity of individual components of the estuary were highly variable and depended on a number of assumptions, which are difficult to validate (Rönnbäck et al ; Minello et al ; Rozas & Minello ). In comparison, estimates at the whole‐of‐estuary level, the seascapes level, in line with current understanding of estuarine species reliance on a mosaic of habitats (Nagelkerken et al ; Sheaves ), required a relatively low number of assumptions and produced estimates with relatively low variability.…”
Section: Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Osmoregulation in C. leucas is achieved through the control and integration of various organs such as the liver and kidney in response to salinity changes. However, little is known regarding the mechanisms of ion transport in the gills of euryhaline C. leucas and how they are affected by osmoregulatory challenges (Hazon et al 2003;Evans et al 2004) Estuaries are biologically diverse and productive ecosystems that provide essential habitats for many fauna and flora including avertebrata, finfish, reptile, and amphibian (Paighambari et al 2017;Abrantes et al 2019). Characterized by shallow water and intertidal areas, including mangrove forests, swamps, saltmarsh, seagrass, intertidal mudflats, and shallow sub-tidal habitats, they are transitional habitats between land and water and freshwater and marine environments (Thomas 2017;Dubuc et al 2019).…”
Section: Contemporary Records and Its Habitatmentioning
confidence: 99%